Impact of fertilisation with sewage sludge on the content of lead in Salix viminalis biomass = Wpływ nawożenia osadami ściekowymi na zawartość ołowiu w biomasie Salix viminalis - Sieciechowicz, Aleksandra; Sadecka, Zofia; Myszograj, Sylwia; Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sewage sludge is considered to be high quality fertilizer. Therefore, in Poland, it is used to fertilize energy plants. On the one hand, it allows using large amount of sewage sludge on the other hand it contributes to the production of renewable energy.
Keywords: ołów; metale ciężkie; osady ściekowe; Salix viminalis; lead; heavy metals; sewage sludge